Impact of Cristiano Ronaldo’s Attractiveness as Brand Ambassador Towards Brand Awareness Shopee - Gunawan, Calvin; Susilo, Daniel (Ekspektra : Jurnal Bisnis dan Manajemen, 2021)
Shopee is one of the consumer-to-consumer (C2C) e-commerce sites in Indonesia. Shopee often collaborates with domestic and international celebrities to become brand ambassadors, one of which is Cristiano Ronaldo. This study aims to determine whether there is an influence and how much influence the attractiveness of Cristiano Ronaldo on Shopee brand awareness. The sample in this study were 400 respondents. The sampling technique in this study was using purposive sampling technique. The data collection method used a questionnaire. The analysis technique used is simple linear regression through SPSS staticstic 24 software. The findings of this study are that there is an influence between the attractiveness of Cristiano Ronaldo to Shopee's brand awareness of 3.3%. The results of this study indicate that the attractiveness of Cristiano Ronaldo has a significant and positive effect on Shopee brand awareness.Keywords: Attraction, Brand Awareness, Shopee.